Teacher identities and English learners in mainstream classrooms: A discourse analysis. Issue 2 (3rd April 2019) - Martin, Adrian D.
ABSTRACT: The increasing placement of English learners (ELs) in mainstream classrooms in conjunction with scant attention given to teaching these students in preservice education and professional development suggests a need to better understand how mainstream teachers understand their professional identities as teachers of these students. The purpose of this qualitative study was to gain insight on how two mainstream teachers of ELs use language to construct their teacher identities and their engagement with EL students. Participants were interviewed multiple times and discourse analysis was employed to analyze their use of language. Overall, their teacher identities possessed a value for ELs being comfortable and welcomed in the classroom. However, participants positioned linguistic differences between ELs and themselves as barriers to learning and communication. The findings suggest a need to move beyond an inclusive disposition toward supporting mainstream teachers to recognize the development of ELs' academic and language progress as integral to their professional identities.